The Creation of the Rule of Law and the Legitimacy of Property Rights : The Political and Economic Consequences of a Corrupt Privatization - Hoff, Karla (World Bank, Washington, DC, 2012)
How does the lack of legitimacy of property rights affect the dynamics of the creation of the rule of law? The authors investigate the demand for the rule of law in post-communist economies after privatization under the assumption that theft is possible, that those who have "stolen" assets cannot be fully protected under a change in the legal regime toward rule of law, and that the number of agents with control rights over assets is large. They show that a demand for broadly beneficial legal reform may not emerge because the expectation of weak legal institutions increases the expected relative return to stripping assets, and strippers may gain from a weak and corrupt state. The outcome can be inefficient even from the narrow perspective of the asset-strippers.